Ethyl acetate extract from red coralline macroalgae Mastophora rosea, rich in polyphenolic catechins, induces apoptosis and inhibits metastasis in melanoma cell line - Eka Sunarwidhi Prasedya; Putu Bella Aprillia Saraswati; Ni Wayan Riyani Martyasari; Andri Frediansyah; Munawar Khalil; Sri Widyastuti (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background The rise in global temperatures and subsequent increase in extreme heatwaves is implicated to have a significant contribution to the growing incidence of various skin diseases, particularly melanoma skin cancer. The existing therapeutic approaches for skin cancer such as chemotherapy induce significant adverse effects. This highlights the need for further development of novel medicinal substances from natural sources which has less side effects implications. Macroalgae, often known as seaweeds, are recognized for their diverse array of bioactive compounds, which have numerous potential applications. The red coralline macroalgae or seaweed Mastophora rosea is abundant in the tropical Indo-Pacific region, including Indonesia. However, little is known regarding the phytochemical profile and potent bioactivity of this unique seaweed. The objective of this study is to assess the phytochemical profile, antioxidant and cytotoxic activity of M. rosea in melanoma cell line. Methodology The dried macroalgae M. rosea sample was extracted using various solvents with differing polarities: ethanol, ethyl acetate (EA), and n-hexane. Subsequent biochemical evaluations included total phenolic content and antioxidant capability. Additionally, cytotoxic experiments were conducted using the mammalian melanoma cell line SK-MEL-2. Results The ANOVA results revealed that the EA solvent was the most efficient in producing extracts with high total phenolic content (368.81 ± 3.16 mg GAE/g). This high total phenolic content is accompanied by potent antioxidant capacity (IC50 = 99.52 ± 19.58 µg/mL). In addition, M. rosea EA extract is attributed with the presence of various polyphenolic catechins, such as gallic acid, gallocatechin, epigallocatechin (EGC), catechin, epicatechin, epigallocatechingallate (EGCG), and epicatechingallate (ECG). Furthermore, M. rosea EA shows strong cytotoxic activity against the melanoma cell line SK-MEL-2 (IC50 = 37.10 ± 0.85 µg/mL). In addition to the melanoma cell line, the M. rosea EA extract shows similar cytotoxicity in epithelial HeLa cells (IC50 = 34.32 ± 1.19 µg/mL) and low cytotoxicity in normal human dermal fibroblast cells (IC50 > 200 µg/mL). Conclusion The current results show that M. rosea could induce apoptosis and also suppress metastasis activity in SK-MEL-2 cells. Further characterization and isolation of the possible bioactive compounds are necessary to better comprehend its mechanism of action against melanoma. Nevertheless, this study indicates that more study needed to be done on various macroalgae regarding their phenolic components that may be beneficial for the development of novel therapeutic agents for cancer treatment. Graphical abstract